2004
DOI: 10.1159/000081591
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Grafting Technique for Patients Unsuited to Heterotopic Transplantation due to Diseased Pelvic Conditions

Abstract: Introduction: An alternative technique for kidney transplantation is presented for patients in whom the use of pelvic vessels is precluded. Patients and Methods: Of 482 cases of kidney or pancreas-kidney transplants, 4 were unsuited to heterotopic grafting, 1 due to multiple operations in the fossae and the 3 others due to extensive vascular occlusive disease. The patients were studied preoperatively by magnetic resonance angiography, which revealed extensive occlusive disease of the distal aorta and/or iliac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
2
3
0
1
Order By: Relevance
“…Our work has revealed that at 12 months, the survival rate was 84.9%. These data are similar to those reported by Musquera et al and Hevia et al [ 2 ] According to the previously reported series by Paduch et al [ 10 ] and Rodrigues et al [ 11 ], graft rates of 100% during follow-up have been informed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our work has revealed that at 12 months, the survival rate was 84.9%. These data are similar to those reported by Musquera et al and Hevia et al [ 2 ] According to the previously reported series by Paduch et al [ 10 ] and Rodrigues et al [ 11 ], graft rates of 100% during follow-up have been informed.…”
Section: Discussionsupporting
confidence: 92%
“…Our work has revealed that at 12 months, the survival rate was 84.9%. ese data are similar to those reported by Musquera et al and Hevia et al[2] According to the previously reported series by Paduch et al[10] and Rodrigues et al[11], graft rates of 100% during follow-up have been informed.According to Ruiz et al, after a mean follow-up of 73.1 months (range 7-312), 80% of the patients who underwent KAT have a functioning graft…”
supporting
confidence: 91%
“…Open surgery for orthotopic kidney transplant has been reported in the literature as an effective alternative for those recipients in whom a heterotopic transplant was inappropriate, such as patients with a retained iliac fossa from a former graft, thrombosis of the iliac vein, or severe arthromatosis on the iliac artery. [15][16][17][18] The long-term patient and graft survival rates are comparable with those for conventional heterotopic kidney transplant. 18 However, open orthotopic kidney transplant has not been the favored approach because it is more difficult when compared with conventional heterotopic kidney transplant.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, two papers described people older than 60 years with multiple comorbidities and severe aortoiliac atherosclerosis [ 23 , 24 ]. Rodrigues et al described four cases (two young people and two older than 60 years old) with severe atherosclerosis [ 25 ]. Furthermore, Chan et al showed three patients (two young and one older than 60 years old) with inferior vena cava (IVC) thrombosis or stenosis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%